Special graphite sealing material for aviation and preparation method thereof
By simplifying the preparation process of special graphite materials, using one-time roasting and one-time impregnation treatment, the problems of cumbersome and high cost in the existing technology are solved, and high-performance special graphite sealing materials for aviation are obtained, with low resistivity and low air pores Characteristics of rate.
Patent Information
- Application Number
- CN202411733389.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The multiple impregnation and calcination processing process in the existing special graphite material preparation process is cumbersome and has high cost, making it difficult to meet the high-performance needs of aviation sealing materials.
The process flow is simplified and production costs are reduced through specific process curves and raw material ratios, including mixing, grinding, pressing, calcining, graphitization, impregnation and purification treatments.
A special graphite sealing material for aviation with high flexural strength, compressive strength, hardness and density is obtained, with low resistivity, porosity and ash content, simplifying the preparation process and reducing production costs.
Smart Images

Figure BDA0005160875520000051 
Figure BDA0005160875520000061 
Figure BDA0005160875520000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of special graphite sealing materials, and in particular relates to a special graphite sealing material for aviation and a preparation method thereof. Background Art
[0002] Special graphite material refers to graphite with a carbon mass fraction greater than 99%, which has high strength, high density and high purity, and is also called "three high graphite". Special graphite sealing materials have the advantages of high temperature resistance, corrosion resistance, pressure resistance and low leakage, so they are widely used in various industrial fields, especially in sealing applications under high temperature, high pressure and corrosive environments, such as in the chemical industry for sealing various chemical containers, pipelines and valves; in the petroleum industry for sealing oil well equipment, pipelines and valves; and in the aerospace industry for sealing engines, hydraulic systems, fuel systems and other equipment.
[0003] In the prior art, a Chinese patent with publication number CN113372118A discloses a method for preparing a special graphite material. The raw materials are Jinzhou needle coke and Baosteel needle coke, which are the most representative of domestic coke in the petroleum system and coal system. The binder is a medium-temperature modified asphalt with a high coking value and strong operability. The process flow is added with a strengthening treatment step after graphitization, and the formula is improved and the control of other steps is improved. The raw material selection is reasonable and the process control is highly targeted. The special graphite material produced by this method has high volume density, high mechanical strength and low thermal expansion coefficient, is suitable for use under high temperature and temperature sudden change conditions, and can be widely used in technical fields such as aerospace, ships, and national defense weapons.
[0004] The Chinese patent with publication number CN118145633A discloses a special graphite material and its preparation method, which comprises kneading, hot rolling and grinding the raw materials in sequence; then pressing the powder; and performing a first roasting treatment on the pressed shaped blank; then performing a cyclic impregnation-roasting treatment on the blank after the first roasting treatment; and finally performing a graphitization treatment on the blank after the cyclic impregnation-roasting treatment. The volume density and graphitization degree of the special-purpose graphite material of the technical solution are significantly improved, and the mechanical strength of the product prepared from the graphite material of the technical solution is high; the self-lubrication and oxidation resistance of the prepared product are good; the microstructure of the material is closer to the theoretical graphite structure, the high-temperature thermal oxidation weight loss rate is low, it can be used in the fields of high temperature resistance and radiation protection, and can significantly extend the service life of the material.
[0005] However, the above technical solutions all use multiple impregnation-calcination treatments during the preparation process, which is cumbersome and costly. Summary of the invention
[0006] In view of the above problems, the present invention provides a special graphite sealing material for aviation and a preparation method thereof. The special graphite sealing material for aviation of the present invention has higher flexural strength, compressive strength, hardness and density; lower resistivity, porosity and ash content; and the preparation process is simpler, thereby reducing production costs.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] The present invention provides a method for preparing a special graphite sealing material for aviation, comprising the following steps:
[0009] S1, kneading and grinding the raw materials in sequence to obtain powder; pressing the powder into a shape to obtain a green body;
[0010] S2, calcining the green body and cooling it to obtain a calcined material;
[0011] S3, sequentially subjecting the calcined material to graphitization treatment, impregnation treatment and purification treatment to obtain a special graphite sealing material for aviation;
[0012] The working curve of roasting is:
[0013] Stage 1: room temperature - 350°C, free heating;
[0014] The second stage: 350-450℃, heating rate 3-5℃ / h;
[0015] The third stage: 450-500℃, heating rate 2-3℃ / h;
[0016] The fourth stage: 500-550℃, heating rate 1.4-1.8℃ / h;
[0017] The fifth stage: 550-750℃, heating rate 1-1.5℃ / h;
[0018] Stage 6: 750-810°C, heating rate 1-3°C / h;
[0019] Stage 7: 810-900°C, heating rate 2-4°C / h;
[0020] Stage 8: 900-940°C, heating rate 4-6°C / h;
[0021] The ninth stage: 940-1200℃, heating rate 8-12℃ / h;
[0022] The tenth stage: 1200±50℃, keep warm for 75-85h.
[0023] In some preferred embodiments, the raw materials, by mass, include 50-55 parts of raw petroleum coke powder, 6-8 parts of natural graphite powder, 24-27 parts of binder, and 12-15 parts of oleic acid mixed solution.
[0024] In some preferred embodiments, the mass ratio of the raw petroleum coke powder to the natural graphite powder is 5-10:1, preferably 7-7.5:1.
[0025] In a preferred embodiment, the raw materials, by mass, include 52.8 parts of raw petroleum coke powder, 7.2 parts of natural graphite powder, 27 parts of binder, and 13 parts of oleic acid mixed solution.
[0026] In a preferred embodiment, the D50 of the raw petroleum coke powder is ≤10 μm, preferably 5-10 μm.
[0027] In some preferred embodiments, the physical properties of the natural graphite powder are: ash content ≤0.5%, moisture ≤1%, volatile matter ≤1%, pH value 6.5-7.5, and sieve particle size -320# is 80-90%.
[0028] Preferably, the natural graphite powder is T399 graphite powder produced by Qingdao Nanshu Ruiying Graphite Co., Ltd.
[0029] In the present invention, +160# represents the powder content with a sieve particle size above the 160-mesh sieve; -320# represents the powder content with a sieve particle size below the 320-mesh sieve.
[0030] In some preferred embodiments, the binder is a mixture of medium-temperature asphalt and coal tar, and the mass ratio of the two is 1-2:2-4, preferably 1-1.5:2.5-3.5, and further preferably 1.4:3.
[0031] In some preferred embodiments, the oleic acid mixed solution is a mixture of oleic acid and alcohol.
[0032] Preferably, the mass ratio of oleic acid to alcohol is 1:100-120.
[0033] In some preferred embodiments, the kneading treatment method is: heat the raw petroleum coke powder, natural graphite powder and oleic acid mixture to 100-120° C. and mix for 120-150 minutes, add a binder (the binder is pre-stirred evenly), and mix for 60-70 minutes with the lid closed.
[0034] In some preferred embodiments, the physical properties of the powder after the grinding process are: ash content ≤ 0.5%, moisture ≤ 1%, volatile matter 15-25%, +160# ≤ 2%, -320# 70-80%.
[0035] In a preferred embodiment, the physical properties of the powder after the grinding process are as follows: ash content is 0.3%, moisture content is 0.7%, volatile matter is 24%, sieve particle size +160# is 1%, and sieve particle size -320# is 77%.
[0036] In a preferred embodiment, the pressing method is cold isostatic pressing.
[0037] Preferably, the cold isostatic pressing pressure is 120-140 MPa, and the time is 8-12 min.
[0038] In a preferred embodiment, the working curve of roasting is:
[0039] Stage 1: room temperature - 350°C, free heating;
[0040] The second stage: 350-450℃, heating rate 4℃ / h;
[0041] The third stage: 450-500℃, heating rate 2.5℃ / h;
[0042] Stage 4: 500-550°C, heating rate 1.67°C / h;
[0043] The fifth stage: 550-750℃, heating rate 1.25℃ / h;
[0044] Stage 6: 750-810°C, heating rate 2°C / h;
[0045] Stage 7: 810-900°C, heating rate 3°C / h;
[0046] The eighth stage: 900-940℃, heating rate 5℃ / h;
[0047] The ninth stage: 940-1200℃, heating rate 10℃ / h;
[0048] The tenth stage: 1200±50℃, keep warm for 80h.
[0049] Preferably, the free heating time is 10 h.
[0050] In some preferred embodiments, the graphitization treatment method is: placing the roasted material in an Acheson graphitization furnace, heating it to 2500-2600° C. by applying power, and the total power-on time is 130-150 hours.
[0051] In some preferred embodiments, the curve of heating after power-on is:
[0052] The first stage: 0-85h, the power increases from 120Kw to 360Kw at a constant speed;
[0053] The second stage: 85-120h, the power increases from 360Kw to 750Kw at a constant speed;
[0054] The third stage: 120-150h, the power drops from 750Kw to 550Kw at a constant speed.
[0055] In some preferred embodiments, the impregnation method is: placing the graphitized product in an impregnation tank, heating it to 200-220° C., keeping it warm for 3-5 hours, adding an impregnating agent, and maintaining the pressure at 1.5-2 MPa for 8-10 hours.
[0056] Preferably, the impregnating agent is impregnating asphalt.
[0057] In some preferred embodiments, the purification method is: placing the impregnated product in a graphitization furnace, supplying chlorine when the furnace core temperature is 2000-2200°C; supplying Freon when the furnace core temperature is 2200-2400°C; and treating at 2800-3000°C for 40-50h.
[0058] Preferably, the purification method is: placing the impregnated product in a graphitization furnace, supplying chlorine when the furnace core temperature is 2000°C; supplying Freon when the furnace core temperature is 2200°C; and treating at 2800-3000°C for 48 hours.
[0059] In some other preferred embodiments, the purification method is: placing the impregnated product in a graphitization furnace, supplying chlorine when the furnace core temperature is 2000-2200°C; supplying chlorine and Freon together after 6 hours; and treating at 2800-3000°C for 40 hours.
[0060] Preferably, during the simultaneous delivery of chlorine and freon, the amount of chlorine is slightly greater than the amount of freon.
[0061] The second aspect of the present invention provides a special graphite sealing material for aviation obtained by the preparation method of the special graphite sealing material for aviation.
[0062] Compared with the prior art, the present invention has the following beneficial effects:
[0063] The preparation method of the special graphite sealing material for aviation provided by the present invention only requires one calcination treatment and one impregnation treatment, the preparation process is simpler, and the production cost is reduced; and the obtained special graphite sealing material for aviation has higher flexural strength, compressive strength, hardness and density; and has lower resistivity, porosity and ash content. DETAILED DESCRIPTION
[0064] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0065] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0066] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0067] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0068] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0069] In the following examples, unless otherwise specified, all raw materials used were commercially available or prepared by conventional methods in the art.
[0070] The sources of raw materials involved in the embodiments and comparative examples are shown in Table 1:
[0071] Table 1
[0072]
[0073]
[0074] Example 1
[0075] Calculated by mass, the raw materials of special graphite sealing materials for aviation use are composed of 52.8 parts of raw petroleum coke powder, 7.2 parts of natural graphite powder, 27 parts of binder (a mixture of medium-temperature asphalt and coal tar, with a mass ratio of 1.4:3), and 13 parts of oleic acid mixed liquid.
[0076] The preparation method of special graphite sealing material for aviation includes the following steps:
[0077] S1. Kneading treatment: heat the mixture of raw petroleum coke powder, natural graphite powder and oleic acid to 110°C and mix for 130 minutes, add the binder (the binder is pre-stirred evenly), and mix for 65 minutes with the lid closed;
[0078] Grinding treatment: 4R Raymond mill is used for grinding to obtain powder; the physical properties of the powder are: ash content is 0.3%, moisture is 0.7%, volatile matter is 24%, +160# is 1%, -320# is 77%.
[0079] Powder pressing: cold isostatic pressing is performed at a pressure of 140 MPa, and the pressure is maintained for 10 minutes and then slowly released to obtain a green body;
[0080] S2, placing the green body in a downdraft kiln for roasting, and cooling to obtain a roasted material; the roasting working curve is:
[0081] Stage 1: room temperature - 350°C, free heating for 10 hours;
[0082] The second stage: 350-450℃, heating rate 4℃ / h;
[0083] The third stage: 450-500℃, heating rate 2.5℃ / h;
[0084] Stage 4: 500-550°C, heating rate 1.67°C / h;
[0085] The fifth stage: 550-750℃, heating rate 1.25℃ / h;
[0086] Stage 6: 750-810°C, heating rate 2°C / h;
[0087] Stage 7: 810-900°C, heating rate 3°C / h;
[0088] The eighth stage: 900-940℃, heating rate 5℃ / h;
[0089] The ninth stage: 940-1200℃, heating rate 10℃ / h;
[0090] Stage 10: 1200±50℃, keep warm for 80h;
[0091] The properties of the calcined material obtained are shown in Table 2: the flexural strength test standard is JB / T 8133.7 Test method for physical and chemical properties of electric carbon products Part 7; the compressive strength test standard is JB / T 8133.8 Test method for physical and chemical properties of electric carbon products Part 8; the resistivity test standard is JB / T 8133.2 Test method for physical and chemical properties of electric carbon products Part 2; the Shore hardness test standard is JB / T 8133.4 Test method for physical and chemical properties of electric carbon products Part 4; the bulk density test standard is JB / T 8133.14 Test method for physical and chemical properties of electric carbon products Part 14; the open porosity test standard is JB / T8133.15 Test method for physical and chemical properties of electric carbon products Part 15.
[0092] Table 2
[0093]
[0094] S3, graphitizing the calcined material in sequence: placing the calcined material in an Acheson graphitization furnace, heating it to 2600°C by powering on; the curve of powering on and heating up is:
[0095] The first stage: 0-85h, the power increases from 120Kw to 360Kw at a constant speed;
[0096] The second stage: 85-120h, the power increases from 360Kw to 750Kw at a constant speed;
[0097] The third stage: 120-150h, the power drops from 750Kw to 550Kw at a constant speed.
[0098] The properties of the graphitized product are shown in Table 3:
[0099] Table 3
[0100]
[0101] Impregnation treatment: Place the graphitized product in an impregnation tank, heat to 210°C, keep warm for 4 hours, add impregnation asphalt, and keep the pressure at 1.8MPa for 9 hours;
[0102] Purification treatment: Place the impregnated product in a graphitization furnace, and supply chlorine when the furnace core temperature is 2000℃; supply Freon at 2200℃; treat at 3000℃ for 48h to obtain special graphite sealing material for aviation.
[0103] Example 2
[0104] The difference from Example 1 is that, by mass, the raw materials of the special graphite sealing material for aviation are composed of 53.9 parts of raw petroleum coke powder, 6 parts of natural graphite powder, 27 parts of binder (a mixture of medium-temperature asphalt and coal tar, with a mass ratio of 1.4:3), and 13.1 parts of oleic acid mixed liquid.
[0105] The working curve of roasting is:
[0106] Stage 1: room temperature - 350°C, free heating for 10 hours;
[0107] The second stage: 350-450℃, heating rate 3℃ / h;
[0108] The third stage: 450-500℃, heating rate 2℃ / h;
[0109] Stage 4: 500-550°C, heating rate 1.4°C / h;
[0110] The fifth stage: 550-750℃, heating rate 1℃ / h;
[0111] Stage 6: 750-810°C, heating rate 1°C / h;
[0112] Stage 7: 810-900°C, heating rate 2°C / h;
[0113] Stage 8: 900-940°C, heating rate 4°C / h;
[0114] The ninth stage: 940-1200℃, heating rate 8℃ / h;
[0115] The tenth stage: 1200±50℃, keep warm for 75h; the rest are the same.
[0116] Example 3
[0117] The difference from Example 1 is that, by mass, the raw materials of the special graphite sealing material for aviation are composed of 50.9 parts of raw petroleum coke powder, 9 parts of natural graphite powder, 27 parts of binder (a mixture of medium-temperature asphalt and coal tar, with a mass ratio of 1.4:3), and 13.1 parts of oleic acid mixed liquid.
[0118] The working curve of roasting is:
[0119] Stage 1: room temperature - 350°C, free heating for 10 hours;
[0120] The second stage: 350-450℃, heating rate 5℃ / h;
[0121] The third stage: 450-500℃, heating rate 3℃ / h;
[0122] The fourth stage: 500-550℃, heating rate 1.8℃ / h;
[0123] The fifth stage: 550-750℃, heating rate 1.5℃ / h;
[0124] Stage 6: 750-810°C, heating rate 3°C / h;
[0125] Stage 7: 810-900°C, heating rate 4°C / h;
[0126] The eighth stage: 900-940℃, heating rate 6℃ / h;
[0127] The ninth stage: 940-1200℃, heating rate 12℃ / h;
[0128] The tenth stage: 1200±50℃, keep warm for 85h; the rest are the same.
[0129] Comparative Example 1
[0130] The only difference from Example 1 is that the T399 graphite powder is replaced with artificial graphite powder of the same quality, and the rest is the same.
[0131] Comparative Example 2
[0132] The only difference from Example 1 is that the raw petroleum coke powder is replaced with needle coke powder of the same mass, and the rest is the same.
[0133] Comparative Example 3
[0134] The only difference from Example 1 is that the mass ratio of raw petroleum coke powder to natural graphite powder is 11.5:1, that is, in parts by mass, the raw materials of special graphite sealing materials for aviation are composed of 55.2 parts of raw petroleum coke powder, 4.8 parts of natural graphite powder, 27 parts of binder (a mixture of medium-temperature asphalt and coal tar, with a mass ratio of 1.4:3), and 13 parts of oleic acid mixed solution.
[0135] Comparative Example 4
[0136] The only difference from Example 1 is that the working curve of the roasting is:
[0137] The first stage: 130-350℃, heating rate 4.4℃ / h, duration 40h;
[0138] The second stage: 350-400℃, heating rate 1.7℃ / h, duration 40h;
[0139] The third stage: 400-500℃, heating rate 1.2℃ / h, duration 80h;
[0140] The fourth stage: 500-600℃, heating rate 1.5℃ / h, duration 70h;
[0141] The fifth stage: 600-700℃, heating rate 3.0℃ / h, duration 35h;
[0142] Stage 6: 700-800℃, heating rate 4.5℃ / h, duration 20h;
[0143] Stage 7: 800-1000°C, heating rate 8.0°C / h, duration 25h;
[0144] The eighth stage: 1000-1250℃, heating rate 8.5℃ / h, duration 30h;
[0145] The ninth stage: 1250±25℃, keep warm for 20h; the rest are the same.
[0146] Comparative Example 5
[0147] The only difference from Example 1 is that the working curve of the roasting is:
[0148] Stage 1: Room temperature -200℃, free heating for 48h;
[0149] The second stage: 200-400℃, heating rate 1℃ / h;
[0150] The third stage: 400-600℃, heating rate 1.5℃ / h;
[0151] Stage 4: 600±10℃, keep warm for 24h;
[0152] The fifth stage: 600-1000℃, heating rate 2.0℃ / h;
[0153] Stage 6: 1000±50℃, keep warm for 72h; the rest are the same.
[0154] Comparative Example 6
[0155] The only difference from Example 1 is that the curve of temperature rise after power on is:
[0156] The first stage: 0-50h, the power increases from 120Kw to 330Kw at a constant speed;
[0157] The second stage: 50-100h, the power increases from 330Kw to 700Kw at a constant speed;
[0158] The third stage: 100-120h, the power drops from 700Kw to 500Kw at a constant speed; the rest remain the same
[0159] Comparative Example 7
[0160] The difference from Example 1 is that, in S3, the calcined material is sequentially subjected to impregnation treatment, graphitization treatment and purification treatment; the rest are the same.
[0161] The performance tests were conducted on the special graphite sealing materials for aviation use of Examples 1-3 and Comparative Examples 1-7. The results are shown in Table 4.
[0162] Table 4
[0163]
[0164] The special graphite sealing material for aviation of the embodiment of the present invention has been applied to a certain type of aircraft engine dynamic sealing device. After application, it has the characteristics of low leakage, low heat generation, long life and high reliability.
[0165] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a special graphite sealing material for aviation, characterized in that: The following steps are involved: S1, kneading and grinding the raw materials in sequence to obtain powder; The powder is pressed into shape to obtain a green body; S2, calcining the green body and cooling it to obtain a calcined material; S3, sequentially subjecting the calcined material to graphitization treatment, impregnation treatment and purification treatment to obtain a special graphite sealing material for aviation; The working curve of roasting is: Stage 1: room temperature - 350°C, free heating; The second stage: 350-450℃, heating rate 3-5℃ / h; The third stage: 450-500℃, heating rate 2-3℃ / h; The fourth stage: 500-550℃, heating rate 1.4-1.8℃ / h; The fifth stage: 550-750℃, heating rate 1-1.5℃ / h; Stage 6: 750-810°C, heating rate 1-3°C / h; Stage 7: 810-900°C, heating rate 2-4°C / h; Stage 8: 900-940°C, heating rate 4-6°C / h; The ninth stage: 940-1200℃, heating rate 8-12℃ / h; The tenth stage: 1200±50℃, keep warm for 75-85h.
2. The preparation method according to claim 1, characterized in that: The raw materials, by mass, include 50-55 parts of raw petroleum coke powder, 6-8 parts of natural graphite powder, 24-27 parts of binder, and 12-15 parts of oleic acid mixed solution.
3. The preparation method according to claim 2, characterized in that: The mass ratio of the raw petroleum coke powder to the natural graphite powder is 5-10:
1.
4. The preparation method according to claim 3, characterized in that: The raw materials include, by mass, 52.8 parts of raw petroleum coke powder, 7.2 parts of natural graphite powder, 27 parts of binder, and 13 parts of oleic acid mixed solution.
5. The preparation method according to claim 4, characterized in that: The D50 of the raw petroleum coke powder is ≤10 μm.
6. The preparation method according to claim 5, characterized in that: The binder is a mixture of medium-temperature asphalt and coal tar, and the mass ratio of the two is 1-2:2-4.
7. The preparation method according to claim 6, characterized in that: The physical properties of the powder after grinding are as follows: ash content ≤ 0.5%, moisture ≤ 1%, volatile matter 15-25%, +160# ≤ 2%, -320# 70-80%.
8. The preparation method according to claim 7, characterized in that: The physical properties of the powder after grinding are as follows: ash content is 0.3%, moisture content is 0.7%, volatile matter is 24%, sieve particle size +160# is 1%, and sieve particle size -320# is 77%.
9. The preparation method according to claim 8, characterized in that: The working curve of roasting is: Stage 1: room temperature - 350°C, free heating; The second stage: 350-450℃, heating rate 4℃ / h; The third stage: 450-500℃, heating rate 2.5℃ / h; Stage 4: 500-550°C, heating rate 1.67°C / h; The fifth stage: 550-750℃, heating rate 1.25℃ / h; Stage 6: 750-810°C, heating rate 2°C / h; Stage 7: 810-900°C, heating rate 3°C / h; The eighth stage: 900-940℃, heating rate 5℃ / h; The ninth stage: 940-1200℃, heating rate 10℃ / h; The tenth stage: 1200±50℃, keep warm for 80h.
10. The preparation method according to claim 9, characterized in that: The method of graphitization treatment is: placing the roasted material in an Acheson graphitization furnace, heating it to 2500-2600° C. by applying power, and the total power-on time is 130-150 hours.
11. The preparation method according to claim 10, characterized in that: The curve of heating after power on is: The first stage: 0-85h, the power increases from 120Kw to 360Kw at a constant speed; The second stage: 85-120h, the power increases from 360Kw to 750Kw at a constant speed; The third stage: 120-150h, the power drops from 750Kw to 550Kw at a constant speed.
12. The preparation method according to claim 11, characterized in that: The purification method is: placing the impregnated product in a graphitization furnace, supplying chlorine when the furnace core temperature is 2000-2200°C; supplying Freon when the furnace core temperature is 2200-2400°C; and treating at 2800-3000°C for 40-50 hours.
13. Special graphite sealing material for aviation obtained by the preparation method according to any one of claims 1 to 12.
Citation Information
Patent Citations
Preparation method of special graphite material
CN113372118A
Special graphite material and preparation method thereof
CN118145633A
Method for preparing large high-power carbon electrode by using semi-graphitized anthracite
CN103864048A
Method for manufacturing large-specification carbon graphite sealing material matrix
CN105777126A
Preparation method of superfine-structure graphite used for electric spark machining
CN107903064A